Electrophysiological properties of ventral cochlear nucleus neurons of the dog - Bal, Ramazan; Baydas, Giyasettin; Naziroglu, Mustafa (Elsevier Science Bv, 2009)
Neurons in the cochlear nucleus (CN) have distinct anatomical and biophysical specializations and extract various facets of auditory information which are transmitted to the higher auditory centres. The aim of the present study was to determine if the principal neurons (stellate, bushy and octopus cells) of the ventral cochlear nucleus (VCN) in 2-week-old dog brain slices share common electrophysiological properties with the principal neurons of mouse VCN. Stellate cells (n = 21, of which three were anatomically identified), fired large, regular trains of action potentials in response to depolarizing current pulses. Input resistance and membrane time constant were 176 +/- 35.9 M Omega (n = 21) and 8.8 +/- 1.4 ms (n = 21), respectively. Bushy cells, (n = 6, of which three were anatomically identified) responded with a single action potential at the onset of depolarizing current steps and showed large hyperpolarizing voltage changes that sag back toward rest to hyperpolarizing current pulses. Input resistance and membrane time constant were 120.4 +/- 56.1 M Omega (n = 5) and 7.6 +/- 2.3 ms (n = 5), respectively. Octopus cells (n = 17, of which seven were anatomically identified) fired a single action potential at the start of a depolarizing current step and exhibited a pronounced depolarizing sag of the membrane potential towards the resting value to hyperpolarizing current steps. Input resistance and membrane time constant were 17.58 +/- 1.3 M Omega (n = 15) and 1.34 +/- 0.13 ms (n = 15), respectively. While stellate cells did not have a threshold rate of depolarization (dV/dt(thresh)), bushy and octopus had a dV/dt(thresh) of 5.06 +/- 1.04 mV/ms (n = 4) and 10.6 +/- 2.0 mV/ms (n = 6), respectively. In octopus cells, the single action potential was abolished by tetrodotoxin (TTX). An alpha-dendrotoxin (alpha-DTX)-sensitive, low-voltage-activated potassium conductance (g(KL)) together with a ZD7288-sensitive, mixed-cation conductance (g(b)) were responsible for the low input resistance, and as a consequence for the brief time constant of the octopus cells. We conclude that the principal neurons of the dog VCN are, as in mouse and cat, distinguishable on the basis of whole-cell patch-clamp recordings. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Auditory pathways; Ventral cochlear nucleus; Patch-clamp; Dog